MSeqDR: A Centralized Knowledge Repository and Bioinformatics Web Resource to Facilitate Genomic Investigations in Mitochondrial Disease. Issue 6 (21st March 2016) - Shen, Lishuang; Diroma, Maria Angela; Gonzalez, Michael; Navarro‐Gomez, Daniel; Leipzig, Jeremy; Lott, Marie T.; van Oven, Mannis; Wallace, Douglas C.; Muraresku, Colleen Clarke; Zolkipli‐Cunningham, Zarazuela; Chinnery, Patrick F.; Attimonelli, Marcella; et al.
Abstract : MSeqDR supports integrated data submission, mining, reporting, and visualization from clinical and research projects related to mitochondrial disease, including phenotypes and whole exome, genome, and mtDNA sequencing data. Integrated data processing pipelines in MSeqDR and Genesis 2.0 Websites call, annotate, and prioritize sequence variants based on phenotypes and functional variant predictions. mtDNA genome analysis tools (Phy‐Mer, MToolBox) predict haplogroup and pathogenicity scores. mvTools and VariantOneStop support automated mtDNA and nuclear variant annotation and submission into MSeqDR‐LSDB. ABSTRACT: MSeqDR is the Mitochondrial Disease Sequence Data Resource, a centralized and comprehensive genome and phenome bioinformatics resource built by the mitochondrial disease community to facilitate clinical diagnosis and research investigations of individual patient phenotypes, genomes, genes, and variants. A central Web portal (https://mseqdr.org ) integrates community knowledge from expert‐curated databases with genomic and phenotype data shared by clinicians and researchers. MSeqDR also functions as a centralized application server for Web‐based tools to analyze data across both mitochondrial and nuclear DNA, including investigator‐driven whole exome or genome dataset analyses through MSeqDR‐Genesis. MSeqDR‐GBrowse genome browser supports interactive genomic data exploration and visualization with custom tracks relevant to mtDNA variation and mitochondrial disease. MSeqDR‐LSDB is a locus‐specific database that currently manages 178 mitochondrial diseases, 1, 363 genes associated with mitochondrial biology or disease, and 3, 711 pathogenic variants in those genes. MSeqDR Disease Portal allows hierarchical tree‐style disease exploration to evaluate their unique descriptions, phenotypes, and causative variants. Automated genomic data submission tools are provided that capture ClinVar compliant variant annotations. PhenoTips will be used for phenotypic data submission on deidentified patients using human phenotype ontology terminology. The development of a dynamic informed patient consent process to guide data access is underway to realize the full potential of these resources.